2019
DOI: 10.1073/pnas.1811516116
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic mechanosensitivity of T cell receptor-mediated spreading of lymphocytes

Abstract: Mechanosensing by T cells through the T cell receptor (TCR) isat the heart of immune recognition. While the mechanobiology of the TCR at the molecular level is increasingly well documented, its link to cell-scale response is poorly understood. Here we explore T cell spreading response as a function of substrate rigidity and show that remarkably, depending on the surface receptors stimulated, the cellular response may be either biphasic or monotonous. When adhering solely via the TCR complex, T cells respond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 45 publications
12
70
0
Order By: Relevance
“…Contemporary approaches in biomaterials design have provided enhanced control over this branch of immunity, leading to new tools for medicine including vaccination and cellular immunotherapy. Intriguingly, tuning the mechanical rigidity of a substrate used to activate T cells can modulate their subsequent functions including cytokine secretion, proliferation, and population expansion (1)(2)(3)(4)(5). These studies have been carried out predominantly in the context of bulk materials that present to cells planar interfaces that are geometrically and mechanically simplistic.…”
mentioning
confidence: 99%
“…Contemporary approaches in biomaterials design have provided enhanced control over this branch of immunity, leading to new tools for medicine including vaccination and cellular immunotherapy. Intriguingly, tuning the mechanical rigidity of a substrate used to activate T cells can modulate their subsequent functions including cytokine secretion, proliferation, and population expansion (1)(2)(3)(4)(5). These studies have been carried out predominantly in the context of bulk materials that present to cells planar interfaces that are geometrically and mechanically simplistic.…”
mentioning
confidence: 99%
“…However, it could be of interest to compare the observed behavior of NK cells to that of other lymphocytes stimulated in analogous conditions. As mentioned above, the effect of surface stiffness on immune activation was previously reported for T cells and B cells, but those reports used relatively short ranges of surface stiffnesses, and showed different stiffness versus activation trends that appeared to depend on the studied stiffness range (14)(15)(16)(17)(18)37) (Table 1). As mentioned, the combination of those studies for T cells suggested the possibility of a bell-shape correlation (6).…”
Section: Results and Discussion Nk Cells Produce Bell-shape Response mentioning
confidence: 85%
“…The comparative use of substrates exhibiting immobilised or mobile anti-CD3 in combination with cytoskeletal drugs evidenced the instrumental role of actin-receptor friction in T cell spreading (Dillard 2014). The same driving force produced by the actin retrograde flow was also proposed, in combination with ligand-receptor force dependent unbinding, to explain the optimal substrate stiffness observed for TCR-mediated spreading (Wahl 2019) (Figure 3C). The interaction of actin and TCR was also proposed to be responsible for TCR triggering by inducing conformational change upon ligand binding (Feng 2017).…”
Section: Cytoskeleton-receptor Interaction and Force Generationmentioning
confidence: 76%
“…The effect of ligand mobility was explored by comparing ligands on fluid lipid bilayers and the same ligands immobilised on glass, maintaining also a precise control and reduction of non-specific interactions (Dillard 2014). The effect underlying substrate stiffness was studied in a wide range using different types of elastomers (Wahl 2019). Patterning and substrate stiffness can also be controlled at the same time (Alameddine 2017).…”
Section: Reductionist and Bio-mimetic Engineering Approachesmentioning
confidence: 99%
See 1 more Smart Citation